AN ANALYSIS OF METONYMY AND METAPHOR IN SELECTED NEWS ARTICLES RELATED TO SPORTS IN THE JAKARTA POST - Indah Utami Chaerunnisah (Prasasti: Journal of Linguistics, 2020)
Since newspapers is a one way communication where they provide information and people receive it, the readers have to be able to understand the whole messages without the chance to clarify and to ask the other parties. This paper aims at revealing the type of metonymy and metaphor used in five selected news articles related to sports in The Jakarta Post, and describing why metonymy and metaphor are used in the news articles. Furthermore, this research is a qualitative research which aims at describing and discussing about the use of metaphor and metonymy in the news articles related to sports. The result revealed that there are only two types of metonymy found in the news articles namely represented entity for representative and whole for part where the most dominant type is represented entity for representative. Furthermore, all types of metaphor can be found in the data, but the most dominant type is structural metaphor. These articles tend to use represented entity for representative since it discusses about athletes and teams which play as the representative of their country. Meanwhile, the dominant use of structural metaphor because the writer tend to describe the athletes and teams as another concrete object.